2018
DOI: 10.11152/mu-1117
|View full text |Cite
|
Sign up to set email alerts
|

Is there a correlation between kidney shear wave velocity measured with VTQ and histological parameters in patients with chronic glomerulonephritis? A pilot study

Abstract: Aim: To analyze the relationship between shear wave velocity in the kidney measured by point shear wave elastography using Virtual Touch Quantification (VTQ) (Siemens Acuson S2000) and histological parameters obtained from renal biopsies, in patients with chronic glomerulonephritis (CGN).Material and methods: The study group included 20 patients (mean age 47.95±13.59 years) with different types of CGN, that had underwent renal biopsy and 57 normal controls (mean age 38.07±17.32 years). In all patients, five va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 26 publications
1
9
1
Order By: Relevance
“…18,19 In native kidneys, the use of point SWE showed similarly no correlation with fibrosis, 20 or even, contrary to the liver, a decrease of KSWS with the progression of renal fibrosis. 9,21 The mean KSWS values obtained in our diabetic patients are lower compared with the mean values that we have found in another study in normal subjects (2.1 vs. 2.3 m/s). 22 Therefore, the question of whether there are other factors influencing KSWS can be raised.…”
Section: Discussioncontrasting
confidence: 83%
“…18,19 In native kidneys, the use of point SWE showed similarly no correlation with fibrosis, 20 or even, contrary to the liver, a decrease of KSWS with the progression of renal fibrosis. 9,21 The mean KSWS values obtained in our diabetic patients are lower compared with the mean values that we have found in another study in normal subjects (2.1 vs. 2.3 m/s). 22 Therefore, the question of whether there are other factors influencing KSWS can be raised.…”
Section: Discussioncontrasting
confidence: 83%
“…In contrast to the above-mentioned studies, Bob et al [ 15 ] reported that the ARFI-e measurement values of the patient group were lower than those of the control group in a study of adult patients diagnosed with GN. Similarly, the renal parenchyma was evaluated with ARFI-e in pediatric patients with CKD by Bilgici et al [ 27 ].…”
Section: Discussionmentioning
confidence: 86%
“…However, the anisotropy of the kidney parenchyma is higher than that of the liver due to its double compartment structure of the cortex and medulla, and also due to its rich vascularization. Therefore, the use of elastography for the evaluation of renal diseases is not widespread [ 15 , 16 ]. Some UE studies have evaluated renal parenchymal diseases, but studies specifically of GN in the pediatric population are limited [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is an increasing trend to differentiate malignant and benign nodules using VTIQ measurement (Liu et al 2016). Its promising diagnostic performance was reported in salivary gland tumors (Zengel et al 2018), chronic glomerulonephritis (Bob et al 2018) and liver fibrosis (Boursier et al 2019). Sun et al (2019) used VTIQ to differentiate benign and malignant breast lesions in a study sample of 252 breast lesions.…”
Section: Discussionmentioning
confidence: 99%